Compositions of enzyme preparations for targeted modification of multicomponent bran - I. S. Vitol; E. P. Meleshkina; L. N. Krikunova (Пищевые системы, 2024)
Microbial enzyme preparations (EPs) of the cellulolytic, proteolytic and phytase action, as well as their compositions, allow obtaining quite a wide spectrum of products of hydrolysis of proteins, non-starch polysaccharides and phytin by means of targeted biocatalysis upon action on grain bran. The use of EPs and multienzyme compositions (MECs) is inherently a modern tool for intensification of biochemical processes underlying one or another food technology. At the same time, EPs allow modifying products of processing plant raw materials, in particular cereal, leguminous and oil-bearing crops (deep processing) and obtain valuable feed and food ingredients. Two multienzyme compositions based on domestic and foreign EPs have been developed and scientifically substantiated. Optimal conditions have been determined for conducting enzymatic reactions when using wheat-lentil-flax bran as a substrate. High effectiveness of the developed MECs has been shown: the proportion of reducing substances (RS) in the hydrolysates under study increased compared to the mass fraction of the autolysates of wheat and three-component bran by 2.8 and 2.3 times (MEC‑1) and by 3.5 and 2.7 times (MEC‑2), respectively. The content of soluble protein increased by 4.7 and 3.0 times (MEC‑1) and by 6.4 and 4.2 times (MEC‑2). The proportion of soluble phosphorus increased on average by 3.0–3.5 times when using MEC‑1 and MEC‑2. It has been found by gel-electrophoresis that the fractions containing low-molecular-weight peptides and free amino acids (MW  < 1000 Da) in the hydrolysates obtained using MECs exceeded by 3–4 times the corresponding fraction in the hydrolysates obtained under the action of endogenous enzymes (autolysis). With that, according to the HPLC results, the concentration of amino acids that are most valuable in terms of nitrogenous nutrition of yeasts (aspartic acid, arginine) increased on average by 2.5–3.0 times, the concentration of valine by 5 times, histidine and isoleucine by 2.0–2.5 times in the experimental hydrolysates of three-component bran.